Network governance as an alternative policy response to managing infectious disease outbreaks: Lessons from Uganda's response to the COVID-19 crisis - Solomon Mwije (wiley, 2023)
Network governance is commended as one of the appropriate approaches to manage infectious disease crises, but knowledge of its implementation is still limited especially in nondemocratic contexts. This study adopted a qualitative case study design using secondary evidence to review how Uganda used network governance to manage COVID-19 crisis. Uganda used the Whole of Government and Whole of Society approaches to form core-periphery networks of government and nongovernment actors. It institutionalized task forces and subcommittees at national, district, and community levels to coordinate the COVID-19 response. Networks of actors contributed to the response through case surveillance and management, enforcement of measures, information sharing, social protection and community engagement, resource mobilization, supply chain management, and vaccination. However, the experiences varied across the country with challenges including consensus problems, mistrust, corruption, poor accountability, abuse of rights, and limited capacities especially in local governments. The study revealed that the effectiveness in handling infectious disease crisis might not greatly depend on the country's democracy but rather the government's ability to recognize the threats and adopt collaborative mechanisms to manage the crisis. Contextual understanding of such experiences may provide lessons that future governments may consider when, not if, crises of such magnitude confront them.摘要
Keywords: complex wicked problems; COVID‐19 response; democracy; network governance; Uganda